RMIL/AG: A new class of nonlinear conjugate gradient for training back propagation algorithm - Basri, S.M.M.; Nawi, N.M.; Mamat, M.; Hamid, N.A. (2018)
The conventional back propagation (BP) algorithm is generally known for some disadvantages, such as slow training, easy to getting trapped into local minima and being sensitive to the initial weights and bias. This paper introduced a new class of efficient second order conjugate gradient (CG) for training BP called Rivaie, Mustafa, Ismail and Leong (RMIL)/AG. The RMIL uses the value of adaptive gain parameter in the activation function to modify the gradient based search direction. The efficiency of the proposed method is verified by means of simulation on four classification problems. The results show that the computational efficiency of the proposed method was better than the conventional BP algorithm.